General Principles and Challenges of Public Administration Organization in Croatia - Staničić, Frane (General Principles and Challenges of Public Administration Organization in Central Europe, 2024)
Public administration in Croatia has been fraught with organizational, political and personal challenges, which are gradually being addressed, particularly through accession to the European Union. Additionally, new reforms have been included in the current (2022–2027) National Plan for Public Administration Development, while the novel concept of wages was introduced in public services. The Constitution distinguishes between State and local authorities by limiting State authority to the right to self-governance. It also establishes mutual relations between the Parliament, government and State administration, as well as local and regional self-governments. Public administration in Croatia can be categorised into State administration, local and regional self-governments, and numerous entities with public authority. A majority of public services can be considered a part of public administration, although employees are not ‘real’ civil servants; they are ‘ordinary’ employees with a rather unique status. The State administration comprises two types of organizational units: ministries and State administrative organizations. Local and regional self-governments comprise municipalities and towns (local) and counties (regional), with local self-governments being particularly fragmented. An important aspect of public administration is the presence of legal entities with public authority, such as public institutions and regulatory agencies, which are sui generis legal forms.KEYWORDS public administration, organization, reforms, State administration, local and regional self-governmentsBibliographyDržavni zavod za statistiku (2022) ‘Objavljeni konačni rezultati Popisa 2021.’, Državni zavod za statistiku, 22 September. [Online]. Available at: https://dzs.gov.hr/vijesti/objavljeni-konacni-rezultati-popisa-2021/1270 (Accessed: 11 November 2023).Đulabić, V., Čepo, D. (2017) ‘Regionalism and Sub-Regional Representation: A Guide to the County Transformation of Croatia’, HKJU-CCPA, 17(4), pp. 539–568 [Online]. Available at: https://doi.org/10.31297/hkju.17.4.2 (Accessed: 10 October 2024). Đulabić, V., Škarica, M. (2012) ‘Regional Policy and the Various Statuses of Local Units in Croatia’, HKJU – CCPA, 12(2), pp. 433–462.European Commission (2022) ‘2022 Country Report – Croatia’, Commission staff working document, 23 May. [Online]. Available at: https://commission.europa.eu/system/files/2022-05/2022-european-semester-country-report-croatia_en.pdf (Accessed: 11 November 2023).European Commission (2024) ‘Economic forecast for Croatia’, European Commission, Directorate-General for Economic and Financial Affairs, 15 November. [Online]. Available at: https://economy-finance.ec.europa.eu/economic-surveillance-eu-economies/croatia/economic-forecast-croatia_en (Accessed: 11 November 2023).Giljević, T., Lalić Novak, G., Lopižić, I. (2021) ‘Croatian Public Administration: Good Governance Accompanied by an Authoritarian Legacy’ in Nemec, J., Reddy, P.S. (eds.) Public Administration in Conflict Affected Countries. Birmingham: Palgarave Macmillan, pp. 217–234; https://doi.org/10.1007/978-3-030-74966-8_11.Godina Hrvatske Statistike (2024) Godina Hrvatske Statistike [Online]. Available at: https://podaci.dzs.hr/hr/ (Accessed: 11 October 2024).Ivanišević, S., Koprić, I., Omejec, O., Šimović, J. (2001) ‘Local Government in Croatia’ in Kandeva, E. (ed.) Stabilization of Local Governments, Local Government and Public Service Reform Initiative. Budapest: Open Society Institute, pp. 179–239.Klarić, M. (2017) ‘Problems and Developments in the Croatian Local Self-Government’, Zbornik radova Pravnog fakulteta u Splitu, 54(4), pp. 807–823 [Online]. Available at: https://doi.org/10.31141/zrpfs.2017.54.126.807 (Accessed: 10 October 2024).Koprić, I. (2005) ‘Djelokrug lokalne i područne (regionalne) samouprave’, Hrvatska i komparativna javna uprava: časopis za teoriju i praksu javne uprave, 5(1), pp. 35–79.Koprić, I. (2008) ‘Managing Public Administration Reform in Croatia’, Hrvatska i komparativna javna uprava: časopis za teoriju i praksu javne uprave, 8(3), pp. 551–565.Koprić, I. (2010) ‘Karakteristke sustava lokalne samouprave u Hrvatskoj’, Hrvatska i komparativna javna uprava: časopis za teoriju i praksu javne uprave, 10(2), pp. 371–386.Koprić, I. (2014a) ‘Prilagodbe hrvatske javne uprave europskim standardima’, Godišnjak Akademije pravnih znanosti Hrvatske, 5(1), pp. 8–39.Koprić, I. (2014b) ‘Problemi s decentalizacijom ovlasti u Hrvatskoj – između ustavnih ovlasti i stvarnosti’, Hrvatska i komparativna javna uprava: časopis za teoriju i praksu javne uprave, 14(1), pp. 133–148.Koprić,  I.  (2016)  ‘Institucionalno  osnaživanje  glavnog  i  velikih  gradova  u  Hrvatskoj  u  funkciji  jačanja  njihovog  kapaciteta  za  regionalnu  suradnju’  in  Osmanković,  J.,  Pejanović,  M.  (eds.)  Mjesto  i  uloga  gradova  SEE  (Jugoistočne  Europe)  u  razvoju  međuregionalne i međudržavne suradnje u okviru Dunavske i Jadransko-jonske evropske makroregije.  Sarajevo:  Akademija  nauka  i  umjetnosti  Bosne  i  Hercegovine,  pp.  3 9 – 5 7.Koprić,  I.  (2018)  ‘Public  administration  characteristics  and  performance  in  EU28:  Croatia’ in Thijs, N., Hammerschmid, G. (eds.) The Public Administration in the EU 28. Luxembourg: Publications Office of the European Union, pp. 101–141.Koprić, I. (2019) ‘Public Administration Reform in Croatia: Slow Modernization during Europeanization  of  Resilient  Bureaucracy’,  Public  Administration  Issues,  Special  Issue I, pp. 7–26 [Online]. Available at: https://doi.org/10.17323/1999-5431-2019-0-5-7-26 (Accessed: 11 October 2024).Koprić, I., Marčetić, G., Musa, A., Đulabić, V., Lalić Novak, G. (2021) Upravna znanost. Zagreb: Pravni fakultet Sveučilišta u Zagrebu, Studijski centar za javne financije, Suvremena javna uprava.Koprić, I., Musa, A., Đulabić, V. (2016) ‘Local Government and Local Public Services in Croatia’ in Wollman, H.,Koprić, I., Marcou, G. (eds.) Public and Social Services in Europe From Public and Municipal to Private Sector Provision. London: Palgrave Macmillan, pp. 201–216; https://doi.org/10.1057/978-1-137-57499-2_14.Ljubanović, B. (2018) ‘European Administrative Standards and Public Administration in  the  Republic  of  Croatia’  in  Tunjica,  P.  (ed.)  EU  and  comparative  law  issues  and  challenges series. Osijek: Faculty of law Osijek, pp. 123–152; https://doi.org/10.25234/eclic/7102.Menger, M. (2019) ‘Explaining Local Self-Government Reorganisation in Croatia: The Garbage  Can  Model  of  Decision-Making’,  Hrvatska  i  komparativna  javna  uprava:  časopis  za  teoriju  i  praksu  javne  uprave,  19(1),  pp.  105–126  [Online].  Available  at:  https://doi.org/10.31297/hkju.19.1.5 (Accessed: 11 October 2024).Ministarstvo  pravosuđa  uprave  (2022)  ’Nacionalni  plan  razvoja  javne  uprave  za  razdoblje od 2022. do 2027. godine’, Ministarstvo pravosuđa uprave, 2022. [Online]. Available   at:   https://mpu.gov.hr/UserDocsImages/dokumenti/Strategije,%20planovi,%20izvje%C5%A1%C4%87a/Nacionalni%20plan%20razvoja%20javne%20uprave%20za%20razdoblje%20od%202022_2027.pdf   (Accessed:   11   September   2023).Musa,  A.  (2013)  ‘Agencies  in  Croatia:  Something  Old  or  Something  New?’,  HKJU  –  CCPA,  13(2),  pp.  353–398  [Online].  Available  at:  https://hrcak.srce.hr/file/192924  (Accessed: 11 October 2024).Musa, A. (2017) ‘Kakva reforma agencija u Hrvatskoj’ in Musa, A. (ed.) Forum za javnu upravu – Javne agencije u potrazi za reformom. Zagreb: Friedrich-Ebert-Stiftung & Institut za javnu upravu, pp. 23–45.Rajko, A. (2016) ‘O značenju pojmova pravna osoba s javnim ovlastima i pravna osoba koja obavlja javnu službu – o važnosti razgraničenja pojmova‘, Informator, 64(6430), pp. 1–3.Škarica, M. (2020) ‘Interplay Between the Tiers in Croatian Local Government: Who Is Winning the Interdependence Game’, Hrvatska i komparativna javna uprava: časopis za teoriju i praksu javne uprave, 20(2), pp. 207–240 [Online]. Available at: https://doi.org/10.31297/hkju.20.2.2 (Accessed: 11 October 2024).Škarica, M., Vukojičić Tomić, T. (2022) ‘Croatia. Games of local democracy in the shadow of national politics’ in Gendźwiłł, A., Kjaer, U., Steyvers, K. (eds.) The Routledge Handbook of Local Elections and Voting in Europe. 1st edn. London: Routledge, pp. 396–407; https://doi.org/10.4324/9781003009672-41.Smerdel, B. (2010) ‘Parlamentarni sustav i stabilnost hrvatskoga Ustava: Slijede li nakon predsjedničkih izbora nove promjene ustrojstva vlasti?’, Zbornik Pravnog fakulteta u Zagrebu, 60(1), pp. 7–44.Smerdel, B. (2013) Ustavno uređenje europske Hrvatske. Zagreb: Narodne novine.The Miroslav Krleža Institute of Lexicography (2024) Croatia: Land and People [Online]. Available at: https://www.lzmk.hr/en/editions/croatia-land-and-people (Accessed: 11 October 2024).Ured za zakonodavstvo (2023) ‘O Uredo’, Ured za zakonodavstvo, 11 November. [Online] Available at: https://zakonodavstvo.gov.hr/o-uredu/9 (Accessed: 11 November 2023).Vlada Republike Hrvatske (2023) ‘Malenica: Zakon o plaćama u državnoj službi prekretnica’, Vlada Republike Hrvatske, 3 July. [Online]. Available at: https://vlada.gov.hr/vijesti/malenica-zakon-o-placama-u-drzavnoj-sluzbi-prekretnica/38628 (Accessed: 11 November 2023).